Living simply : a teen guide to minimalism - McGraw, Sally (Twenty-First Century Books, 2019)
Presents an exploration of what it means to live minimally, how a minimalist lifestyle helps the environment, and what teenage readers can do to adopt and begin to love a minimalist lifestyle. Includes a glossary.